Enhancing Citizens’ Participation in Planning and Budgeting in Kibaha Town Council, Tanzania - Malipula, Mrisho M (UI Scholars Hub, 2022)
Citizens’ participation is deemed key in the planning and budgeting of developmental activities, but grassroots participation in such endeavors has proven problematic. Against such a backdrop, this study examined citizens’ participation in planning and budgeting processes in local governments. It explores the nature and level of citizens’ participation in planning and budgeting, as well as challenges impeding their participation in the same KTC. The study employed a qualitative stakeholder analysis that involved a sum of 42 interviewees. 24 participated in 3 FGDs involving women, youth, and farmers, and 18 as Key Informants purposively picked among Councillors, WDC members, CSO leaders, and KTC officials with knowledge of planning and budgeting processes. A desk review was employed to triangulate FGDs and KIIs findings. The data garnered in this study underwent thematic content analysis and was descriptively discussed. The study unveils that space for local participation in KTC is diminutive and most of the Kibaha inhabitants neither have a proper understanding of their Council’s planning and budgeting processes nor the ability to informally participate in the same. Equally, procedures and structures for community engagement for effective citizens’ participation in the monitoring and evaluating of development interventions hardly exist. Such a situation constrains the promotion of effective, responsive, and responsible government at the local level. In light of the weaknesses highlighted, this article calls for deliberate efforts to build capacities and create space for citizen participation to meet the objective of decentralization and fast-track improved public service delivery in Tanzania.